PEMBAGIAN HARTA WARISAN ALMARHUM MARABEN DAN MEIDA SM M PANGGABEAN MENURUT KUHPERDATA (STUDI PUTUSAN NOMOR 151/PDT.G/2020/PN JKT PST) - Tantri Benaz Cindy Siregar; Dinda Keumala (Fakultas Hukum Universitas Trisakti, 2021)
Regarding Decision Number 151/Pdt.G/2020/PN Jkt Pst where there was a dispute over the inheritance of the late Retired General Maraben and Meida SM M Panggabean, thus making the author to conduct further research with the formulation of the problem of how the distribution of the inheritance of the late Retired General Maraben and Meida SM M Panggabean to their heirs according to the Civil Code, and whether the contents of Decision Number 151/Pdt. G/2020/PN Jkt Pst regarding the division of the estate of the late Retired General Maraben and Meida SM M Panggabean is in accordance/not according to the Civil Code. The research was normative legal method, descriptive analytical, secondary data type, conducted qualitatively, deductive logic inference. The results of research, discussion and conclusions: the distribution of the estate of the late Retired General Maraben and Meida SM M Panggabean to their heirs according to the Civil Code, namely Duma (3/16) part, Musida (3/16) part, Tetty (3/16) part and Baringin (7/16) part and the contents of Court Decision Number 151/Pdt.G/2020/PN Jkt Pst regarding the distribution of the estate of the late Retired General Maraben and Meida SM M Panggabean to their heirs are not in accordance with the Civil Code.